2016
DOI: 10.1371/journal.pone.0165278
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Alcohol Consumption and Smoking and the Risk of Major Gastrointestinal Bleeding in Men

Abstract: Background and AimsData regarding smoking and alcohol consumption and risk of gastrointestinal bleeding (GIB) are sparse and conflicting. We assessed the risk of major GIB associated with smoking and alcohol consumption in a large, prospective cohort.MethodsWe prospectively studied 48,000 men in the Health Professional follow-up Study (HPFS) who were aged 40–75 years at baseline in 1986. We identified men with major GIB requiring hospitalization and/or blood transfusion via biennial questionnaires and chart re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 52 publications
1
16
0
5
Order By: Relevance
“…26 One prospective study including 48,000 men did not find an increased risk of major gastrointestinal bleeding among current or past smokers or in relation to pack-years of smoking. 27 However, another prospective including 5,888 elderly men and women found that current smokers had a higher risk of hospitalization for gastrointestinal bleeding than non-smokers. 28 To the best of our knowledge, no studies have examined the association between smoking and airway bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…26 One prospective study including 48,000 men did not find an increased risk of major gastrointestinal bleeding among current or past smokers or in relation to pack-years of smoking. 27 However, another prospective including 5,888 elderly men and women found that current smokers had a higher risk of hospitalization for gastrointestinal bleeding than non-smokers. 28 To the best of our knowledge, no studies have examined the association between smoking and airway bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest that alcohol consumption is typically associated with increased risk of GIB, particularly from peptic ulcer disease. 19 In the prospectively collected database, which incorporates details from other institutions' records, GIB patients were more likely to be anemic, have a coagulopathy, be malnourished, and have a chemical dependency. This is associated with known risk factors for GIB, which include non-GI comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency laparoscopic patch repair was undertaken, and he made an uneventful recovery, with referral to alcohol dependence services. Risk factors for peptic ulcerative disease include helicobacter pylori infection (48%), 1 NSAID use (24%), 1 smoking (23%), 1 and alcohol excess (43%), 2 which was likely an important contributing factor in this patient.…”
Section: Case Descriptionmentioning
confidence: 95%